Maximising the wrench capability of mobile manipulators with experiments on a UVMS - Marais, Wilhelm J.; Pizarro, Oscar; Williams, Stefan B. (Frontiers in Robotics and AI, 2025)
This paper presents methods for finding optimal configurations and actuator forces/torques to maximise contact wrenches in a desired direction for underwater vehicle manipulator systems (UVMS). The wrench maximisation problem is formulated as a bi-level optimisation problem, with upper-level variables in a low-dimensional parameterised redundancy space, and a linear lower-level problem. We additionally consider the cases of one or more manipulators with multiple contact forces, maximising the wrench capability while tracking a trajectory and generating large wrench impulses using dynamic motions. The specific cases of maximising force to lift a heavy load and maximising torque during a valve-turning operation are considered. Extensive experimental results are presented using a 6 degree of freedom (DOF) underwater robotic platform equipped with a 4DOF manipulator and show significant increases in the wrench capability compared to existing methods for mobile manipulators.